THE FAILED INSTITUTIONALIZATION OF GENDER EQUALITY UNDER LOCAL ELITE CAPTURE IN VILLAGE GOVERNANCE STRUCTURES - Hartika Arbiyanti; Afgan Fadilla; Surfian Rahmat AP; Fullah Jumaynah; Chomariyana Kartika Hesti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The decentralization of village governance is expected to create inclusive democratic spaces and promote gender equality at the grassroots level. However, these normative ideals frequently collide with the reality of local power dynamics. Based on a critical literature review, this article investigates how local elite capture and rent-seeking motives hijack gender mainstreaming policies in village governance. The study finds that in the planning phase (Musrenbangdes), women's participation is reduced to